2015
DOI: 10.1371/journal.pone.0135470
|View full text |Cite|
|
Sign up to set email alerts
|

R54C Mutation of NOTCH3 Gene in the First Rungus Family with CADASIL

Abstract: Cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL) is a rare hereditary stroke caused by mutations in NOTCH3 gene. We report the first case of CADASIL in an indigenous Rungus (Kadazan-Dusun) family in Kudat, Sabah, Malaysia confirmed by a R54C (c.160C>T, p.Arg54Cys) mutation in the NOTCH3. This mutation was previously reported in a Caucasian and two Korean cases of CADASIL. We recruited two generations of the affected Rungus family (n = 9) and found a missense … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…However, other studies such as those in eastern and southern China, Taiwan and Korea showed a different result, with the majority being mutations in exon 11 [2][3][4]. The neuroimaging features in these studies were also different, with a lower percentage (20-45.8%) of anterior temporal pole involvement and a higher prevalence of intracranial haemorrhage [3,4,7] Previous reported genetically confirmed cases from Malaysia include a Rungus family [8] and a Chinese Malaysian family who resides in Singapore [5]. In concordance with the multiethnic diversity of the country, this case series highlights the variations in genotypes and phenotypes among various ethnic groups in Malaysia.…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…However, other studies such as those in eastern and southern China, Taiwan and Korea showed a different result, with the majority being mutations in exon 11 [2][3][4]. The neuroimaging features in these studies were also different, with a lower percentage (20-45.8%) of anterior temporal pole involvement and a higher prevalence of intracranial haemorrhage [3,4,7] Previous reported genetically confirmed cases from Malaysia include a Rungus family [8] and a Chinese Malaysian family who resides in Singapore [5]. In concordance with the multiethnic diversity of the country, this case series highlights the variations in genotypes and phenotypes among various ethnic groups in Malaysia.…”
Section: Introductionmentioning
confidence: 80%
“…To have a more complete profile of a Malaysian case series, two previously reported Malaysian families were included in the analysis, consisting of a Rungus family reported by Lim et al [8] and a Malaysian Chinese family by Wilder-Smith et al [5].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation